TATA KELOLA ASET BARANG MILIK DAERAH BERBASIS E-BMD PADA DINAS PERTANIAN KOTA KENDARI - Muhammad Jabbal Nur; Muhammad Ihsan Mattalitti; Riston G. Ahmad (Halu Oleo University, 2024)
This study aims to provide an in-depth overview of the implementation of the E_BMD system in the Kendari City Agriculture Service using qualitative descriptive methods. The results of the study indicate that the implementation of the E-BMD system significantly increases efficiency in the management of Regional Property (BMD). Starting from identification to asset disposal. This system facilitates real-time asset recording, increases accuracy, and transparency and facilitates a more transparent and accountable asset procurement process. Although there are obstacles to employee understanding of technology, E-BMD also allows automatic maintenance scheduling, although limited human resources and budget constrain its implementation. In asset disposal, this system helps accelerate the process of eliminating unusable assets, although employee training still needs to be improved. Overall, E-BMD has great potential to increase efficiency, transparency and accountability in regional asset management. However, optimization requires increased human resource competency and improved coordination between agencies. Recommendations include ongoing training for employees and increased budget allocation to support the operation and maintenance of the system on an ongoing basis. These findings indicate that with the right steps, E-BMD can be optimized to support more effective and efficient asset management in the future.